1993
DOI: 10.1039/c39930000523
|View full text |Cite
|
Sign up to set email alerts
|

Novel ceramic and organometallic depolymerization products from poly(ferrocenylsilanes)via pyrolysis

Abstract: When heated at 500°C under nitrogen the poly(ferrocenylsi1anes) [ F~(Y-C~H~)~(S~R~) ]~

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 10 publications
2
58
0
Order By: Relevance
“…[7,9±11] In addition, heating to 500±1000 C can yield magnetic ceramics containing a-Fe crystallites and oxidation has been reported to yield materials that display spin alignment, albeit at low temperatures. [12,13] Although thermal ROP gives rise to high molecular weight (M n > 10 5 ) materials there is virtually no chain length control and the molecular weight distributions are broad. We have therefore been very interested in the development of more controlled ROP routes, particularly those which would allow access to multiblock architectures with their associated phase-separated, redox-active domain structures.…”
Section: Living Anionic Rop Of Metallocenophanesmentioning
confidence: 99%
“…[7,9±11] In addition, heating to 500±1000 C can yield magnetic ceramics containing a-Fe crystallites and oxidation has been reported to yield materials that display spin alignment, albeit at low temperatures. [12,13] Although thermal ROP gives rise to high molecular weight (M n > 10 5 ) materials there is virtually no chain length control and the molecular weight distributions are broad. We have therefore been very interested in the development of more controlled ROP routes, particularly those which would allow access to multiblock architectures with their associated phase-separated, redox-active domain structures.…”
Section: Living Anionic Rop Of Metallocenophanesmentioning
confidence: 99%
“…[66] Magnetic Ceramics on the Nanometer Scale As discussed above, polyferrocenylsilanes function as pre-ceramic polymers and have been shown to yield interesting magnetic ceramic composites at 500 -1000 8C which contain small Fe particles embedded within a SiC/ C matrix. [69] In collaboration with the group of G. A. Ozin we have explored the pyrolysis of polyferrocenylsilanes within the channels of the mesoporous silica MCM-41 with the aim of accessing nanostructured magnetic ceramic materials (Figure 7). [70] During our initial studies of the formation of composite MCM-41 materials with polyferrocenylsilanes we found that monomer 1 (R = R9 = Me) can be sublimed into the hexagonal mesopores of MCM-41 at room temperature with a maximum loading of 74% of monomer to host.…”
Section: Organometallic and Magnetic Ceramic Microspheresmentioning
confidence: 99%
“…• .O3 vi 3.34 (3) et al, 1993), (b) supramolecular chemistry (Beer et al, 1991), (c) non-linear optical materials science (Houlton et al, 1993), (d) ceramics (Tang et al, 1993) and (e) molecular-inclusion and recognition chemistry (Ferguson, Gallagher, Glidewell & Zakaria, 1994a,b). Hydrogen bonds often provide the strongest intermolecular forces between molecules in organic molecular crystals and hence often dictate the preferred packing arrangement.…”
mentioning
confidence: 99%